DAMPAK COVID-19 TERHADAP PENDAPATAN MARINA BAKERY: BERADAPTASI DENGAN PERUBAHAN PREFERENSI KONSUMEN - Pratiwi, Lily Indah; Pujianto, Pujianto; Purwaningsih, Endah Supeni (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2024)
The Covid-19 pandemic has significantly impacted the income of Marina Bakery, a home-based MSME in Surabaya, East Java, specializing in bread production. Despite its potential to produce various products based on customer demand, especially targeting the low-cost bread market for events and celebrations, the limitations on social gatherings caused by the pandemic have led to a decline in the bakery's income. In order to continue its business, Marina Bakery must explore new growth strategies. By diversifying its product offerings to include options that suit customer needs, such as changing individual or family portion sizes that are suitable for consumption at home, the bakery can continue to maintain its business. In addition, expanding marketing through brand image strategies and creating good financial records can help Marina Bakery's business sustainability. The implementer of the community service activity will partner with Marina Bakery in providing assistance and training related to the problems that have been carried out on June 19, 2024, July 16, 2024, and August 8, 2024. The purpose of this training and assistance is for Marina Bakery to understand the importance of business development by adapting according to customer tastes or preferences, the importance of marketing with a brand image strategy, and knowing the importance of good business financial management. It is hoped that Marina Bakery can overcome current obstacles and maintain the sustainability of its business in the affordable bread market while exploring new revenue streams.Keywords: